Analisis User interface Software Corel Draw X7 Menggunakan Metode 8 Golden Rules of Interface Design - Bangga Alansyah; Diana Khuntari (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
The advancement of science and technology in society has become an important need, impacting the improvement of human resource quality and the emergence of new fields such as Visual Communication Design (DKV). One form of DKV development is User interface (UI), which helps users get information and interact with products. In supporting design processing, software assistance is needed, one of which is CorelDraw X7. To determine the quality of the CorelDraw X7 UI, an analysis was carried out using the theory of 8 Golden Rules of Interface Design which has indicators: Strive For Consistency, Seek Universal Usability, Offer Informative Feedback, Design Dialogs to Yield Closure, prevent errors, Permit Easy Reversal of Actions, Keep Users in Control, and minimize short-term memory load. The results of this study using the descriptive qualitative method show that the CorelDraw X7 UI is in the good category. Three indicators, namely Strive For Consistency, Seek Universal Usability, and Permit Easy Reversal of Actions, are applied optimally. Four indicators are applied well but not optimally, namely Offer Informative Feedback, prevent errors, Keep Users in Control, and minimize short-term memory load. The Design Dialogs to Yield Closure indicator is in the less than good category. Suggestions for improvement include reducing feedback delay, updating the status bar icon, adding languages ​​other than English-US, and updating the toolbox icon to reduce errors in selecting tools.